Work-Family facilitation and family satisfaction as mediators in the relationship between job demands and intention to Stay - Noraani Mustapha; Aminah Ahmad; Jegak Uli; Khairudin Idris (2011)
Employee turnover has been a major concern among researchers in human resource development (HRD) area since it has negative impact on organization. This study was conducted to test the mediating effects of work-family facilitation and family satisfaction on the relationship between job demands as the independent variable and intention to stay as the dependent variable. Data was collected from 240 middle age single mother employees by using self-administered research questionnaire. Samples were determined through simple random sampling method whereby six out of 24 single mother associations were selected to obtain research samples. Descriptive statistical analysis was conducted to describe the demographic characteristics of respondents. Pearson Product Moment Correlation was used to determine the relationships among variables and Structural Equation Modeling using AMOS version 16.0 was utilized for model testing and to verify the presence of mediation effects. Then the Sobel’s z-test was used to examine whether the mediators carry the effect of the independent variable on the dependent variable. The findings indicated that there were positive relationships among variables. The results also established the presence of mediation effects between the independent and dependent variables. Organizations may utilize job demands factor, work-family facilitation and family satisfaction as mechanisms to promote longer retention among employees.